BIODIVERSITY OF ADULT FEMALE MOSQUITOES: ACTIVE SURVEILLANCE TO ADDRESS MOSQUITO-BORNE DISEASES IN CIMAHI, INDONESIA - Lia Faridah; Muhammad Akbar Thufail; Ridha Beta Zahra; Nisa Fauziah; Annisa Abdiwijaya Qaromah; Kozo Watanabe (Medika Kartika : Jurnal Kedokteran dan Kesehatan, 2026)
Mosquito-borne diseases are a global health threat, especially in developing cities such as Cimahi City, West Java, which has shown an increase in cases of dengue fever and filariasis. Limited data on adult mosquito vectors in Cimahi prompted this exploratory descriptive study. A total of 439 female mosquitoes were collected from 15 villages during the dry and rainy seasons using light traps, then identified morphologically. Diversity analysis was conducted using the Shannon-Wiener index (H'), while comparisons between locations were performed using the Kruskal-Wallis test due to non-normal data distribution. The results showed that Culex spp. (54.67%) dominated, followed by Aedes aegypti (32.19%), Armigeres spp. (10.02%), and Aedes albopictus (3.19%). Baros had the highest number of mosquitoes (77), while Central Cimahi had the lowest (11). The majority of villages showed low diversity (H' ≤ 1) and uneven distribution (J < 0.5) with the dominance of certain species. The Kruskal-Wallis test found no significant difference in the number of mosquitoes between villages (p = 0.993). Keywords: Cimahi City, mosquito diversity, mosquito-borne diseases DOI : 10.35990/mk.v9n1.p68-78